The Ideology and Implementation of Aesthetic Education in Junior High School of Semarang Municipality - Rondhi, Mohammad; Soesanto, Soesanto; Sugiharto, Ignatius Bambang (The Journal of Educational Development, 2018)
Aesthetic education is an aspect of art education in schools whose implementation is very diverse. The diversity in the implementation is thought to be due to differences in the teacher’s ideology on aesthetic education. The teacher's perception of aesthetic education must be influenced by the ideology he/she embraces. Therefore, field research is needed to provide an explanation of the teacher’s ideology and the implementation of aesthetic education at school. Problems to be solved through this research were (1) how is the ideology and understanding of teacher’s art about aesthetic education and (2) how is the implementation of aesthetic education at school. This research utilized a qualitative approach with cultural ecology model. Data were collected by observation, interview, and documentation techniques. The target of this research was art and culture teachers of Junior High School in Semarang. The results showed that in carrying out the learning of art and culture all teachers refer to the school-based (KTSP) curriculum and the 2013 Curriculum. Almost all art and cultural teachers carry out the learning process in accordance with the guidelines of the curriculum although they still adjust to school conditions. According to the art and culture teachers, in fact, the substance of the two curricula is not very much different; both are based on students and learning strategies using a scientific approach. In addition to providing an aesthetic experience to students, art education is also very appropriate as a means of character education for the nation.